2022
DOI: 10.1186/s12912-022-01091-x
|View full text |Cite
|
Sign up to set email alerts
|

Workplace sexual harassment toward male nurses in South Korea: a cross-sectional online survey

Abstract: Background Many studies have focused on sexual harassment of female nurses perpetrated by patients and coworkers. However, as males in a female-dominated occupation, male nurses are also at risk of being exposed to sexual harassment. The aim of this study was to examine the prevalence of workplace sexual harassment faced by male nurses in South Korea and to identify related factors. Methods A cross-sectional study was conducted using an online surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Perhaps, nurses need sexual harassment education. Although comparing the prevalence of sexual harassment among different studies and countries could be misleading due to various contextual factors,32 39 our findings suggest that the prevalence of workplace sexual harassment against nurses in the Central Region is unacceptably high. This calls for further and comprehensive studies on the phenomenon and the implementation of antisexual harassment policies in the healthcare sector to help reduce the occurrence of sexual harassment against nurses in the region.…”
Section: Discussionmentioning
confidence: 71%
“…Perhaps, nurses need sexual harassment education. Although comparing the prevalence of sexual harassment among different studies and countries could be misleading due to various contextual factors,32 39 our findings suggest that the prevalence of workplace sexual harassment against nurses in the Central Region is unacceptably high. This calls for further and comprehensive studies on the phenomenon and the implementation of antisexual harassment policies in the healthcare sector to help reduce the occurrence of sexual harassment against nurses in the region.…”
Section: Discussionmentioning
confidence: 71%
“…Research (Jeong & Chang, 2022) reveals that harassment does not only occur to women but also to men. The findings reveal a sexual prevalence of harassment, with 65.2% of male nurses having experienced sexual experience harassment at least once during the past six months at their workplace.…”
Section: Sexual Harassmentmentioning
confidence: 99%
“…Passive responses about sexual harassment also happened to the male victim. Jung's findings (Jeong & Chang, 2022) revealed that more than half of the male nurses remained passive in sexual response harassment, "laughing at it" (32.3%), "not expressing anything" (12.5%), and "avoiding the situation" (9.4%), while 15.6% of respondents actively responded and expressed displeasure. In addition, most male nurses (91.1%) did not report SH incidents, with the most frequent reason for not reporting (58.9%) being that they did not expect reporting to result in any change.…”
Section: Sexual Harassmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As males in a femaledominated occupation, male nurses are at risk of being exposed to sexual harassment and a recent study from South Korea sought to examine the prevalence of workplace sexual harassment faced by male nurses in South Korea and to identify related factors. 4 Based on an online survey, they found that 65.2% of male nurses had experienced sexual harassment at least once during the past 6 months at their workplace. Mistreatment because of gender, repeated sexual stories or jokes, and comments about appearance were the most frequent forms of harassment experienced.…”
mentioning
confidence: 99%